2018
DOI: 10.1590/0034-7167-2017-0192
|View full text |Cite
|
Sign up to set email alerts
|

Error-producing conditions in nursing staff work

Abstract: The errors made by nursing staff workers demonstrate that error-producing conditions are present in the context of their occurrence in all actions, and understaffing and intensity of work are the most recurrent circumstances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 11 publications
0
7
0
5
Order By: Relevance
“…Attention to patient identification is not only important for the patient, but also for the safety of the professionals, since everyone involved in the care process suffers from the implications of a patient safety incident. Therefore, updating professional knowledge is extremely valuable for their protection and for patient safety, especially for professionals working in sectors that have particularities, such as pediatrics, which requires specific actions aimed at this public (19) .…”
Section: Discussionmentioning
confidence: 99%
“…Attention to patient identification is not only important for the patient, but also for the safety of the professionals, since everyone involved in the care process suffers from the implications of a patient safety incident. Therefore, updating professional knowledge is extremely valuable for their protection and for patient safety, especially for professionals working in sectors that have particularities, such as pediatrics, which requires specific actions aimed at this public (19) .…”
Section: Discussionmentioning
confidence: 99%
“…Refs. 28 argued that the occurrence of error was not only related to the individual attitude of the worker, but the working conditions provided by the employer, such as equipment and materials, infrastructure, work process, salary, working hours, number of employees, job satisfaction, job stability, also affect job performance. Refs.…”
Section: Background and The Related Workmentioning
confidence: 99%
“…[6] From this perspective, hospital institutions are increasingly concerned with ensuring safe care, offering excellent care, reducing costs, and ensuring customer satisfaction. [7,8] A study carried out in the south of Minas Gerais showed that the nurse's praxis in patient safety in the hospital environment is consolidated through leadership, the exercise of nursing management, and care based on communication with a focus on empathy, dialogue and in valuing strategies for continuing and permanent education. [8] Therefore, hospitals have incorporated the aim of instituting safety as a cultural process, promoting greater awareness of professionals regarding the culture of safety and an ethical commitment in risk management, with the consequent acquisition of safety for themselves and the clients, overcoming the existing gap in the aspect of patient safety.…”
Section: Introductionmentioning
confidence: 99%